Differences of bisphenol analogue concentrations in indoor dust between rural and urban areas. (August 2021) - Liu, Daxi; Wu, Pengfei; Zhao, Nan; Nie, Saisai; Cui, Jiansheng; Zhao, Meirong; Jin, Hangbiao
Abstract: Bisphenol analogues (BPs) are widely applied in varying consumer products. Many studies have reported their presence in indoor dust samples from China. However, the differences in occurrence and concentration profiles of BPs in indoor dust between rural and urban areas are still not well characterized. In this study, eight BPs were measured in 60 indoor dust samples collected from rural and urban districts of Hangzhou, China. Bisphenol A (BPA; mean 1.8 μg/g, range 0.20–7.2 μg/g) was the predominant BP in indoor dust samples, accounting for mean 57% of the total BP (∑BP) concentration, followed by bisphenol S (BPS; 0.58 μg/g, <LOD–2.4 μg/g) and bisphenol AF (0.43 μg/g, <LOD–2.6 μg/g). Indoor dust samples from the urban areas ( n = 27) contained significantly ( p < 0.05) higher levels of ∑BPs, BPA, and BPS than that from the rural areas ( n = 33). Comparatively, bisphenol F and bisphenol AP were more frequently detected in urban indoor dust samples. Daily intakes (DIs) of BPs through the indoor dust inhalation were estimated for infants, children, and adults. Infants had much higher ( p < 0.01) DIs of BPs than children and adults, mainly owing to their lower body weights and higher indoor dust ingestion rates. To our knowledge, this is one of the first studies examining the regional differences of BP concentrations in indoor dust from China, which could contribute to the more accurate evaluation of human BP exposure through indoor dust intake. Highlights: BPA, BPS, and BPAF were the major BPs in indoor dust samples from Hangzhou. Indoor dust from urban areas contained higher concentrations of BPA and BPS. BPF and BPAP were more frequently detected in urban indoor dust samples. Infants had much higher daily intakes of BPs than children and adults.